ENTREPRENEURSHIP: Soft Skill of Life - Mahmudin Mahmudin; Agus Caesario; Aman Saputra (Jurnal PKM Manajemen Bisnis, 2021)
When a person becomes an adult, then in fact he has become a person who is independent of himself. So the consequence of being an adult is, to live life with the sweat. Therefore, preparation is needed to become an independent life, one of which is to have survival skills, namely doing business. This service activity is carried out as a concern for the life of the surrounding community, especially teenagers, to provide information and expertise that can be useful for their lives in the future. This service activity contains learning activities, training and entrepreneurial practice, thus helping teenagers understand the basic concepts of establishing a business. This activity was carried out in Pamulang District (South Tangerang), and the participants in the activity were teenagers in the Reni Jaya housing estate. The activity was carried out for three days, with an agenda of learning theory, learning practice, and sharing experiences from business actors. Obviously, this activity creates enthusiasm for entrepreneurship, this can be seen in the enthusiasm of the participants in participating in activities, asking lots of questions, and being careful in participating in activities. In addition, this activity can increase the knowledge, knowledge, and interest of young people in establishing a business as a way to live their lives in the future.